Mysterious faces of hybridisation: an anticipatory approach for crisis literacy - Karjalainen Joni; Heinonen Sirkka; Taylor Amos (Springer, 2025)
Our complex world is changing at such a pace that we are struggling to address many of the global challenges ahead of us. As one of its symptoms, hybridisation means that fields, functions, characteristics and roles are increasingly combined and fused. This paper is an opening to the study of hybridisation, as an overlooked topic in the field of futures studies and foresight. We explore how hybridisation could be integrated into foresight through identification and interpretation of emerging issues and weak signals. As our case study, we examined how hybridisation manifests in the urban texture. We performed an anticipatory analysis of three hybrid urban spaces of pioneering architecture. We assumed a view to hybridity that considered diverse futures, images of the future, and open futures to detect what is opening or closing. Coming to terms with hybridisation and its expressions may inform action on anticipatory governance by improving the detection of opportunities, risks and crises. Deeper understanding of budding developments that removes ambiguity may be a nudge towards novel solutions and promote futures resilience.